Drones prove their worth in measuring livestock methane in Africa - Arndt, Claudia; Hove, A.; Slater, Annabel; Fava, Francesco P. (International Livestock Research Institute, 2025)
This blog presents results from the first successful application of drone-mounted sensors to measure methane emissions from grazing livestock in Africa. Drone measurements over cattle, sheep, goats, and camels under real-world conditions demonstrated that the approach can reliably detect methane concentration gradients and temporal emission patterns. The work shows how drone-based measurements can complement satellite and ground-based data to strengthen national greenhouse gas inventories and support the assessment of methane mitigation strategies in African livestock systems.